THE ERGONOMIC NATURE OF THE MULTIMEDIA PRESENTATION AS A SUBJECT OF ASSESSMENT - Dieorditsa, Taiana; Bilevych, Svitlana; Voronina, Maryna; Hladushyna, Raisa (Physical and Mathematical Education, 2023)
Formulation of the problem. According to our observations, student multimedia presentations often lack ergonomic elaboration. Intending to teach students self-assessment of the ergonomic nature of these multimedia objects, we wondered: what characteristics of a multimedia presentation are the basis for judging its ergonomic level as acceptable? Materials and methods. The guiding ideas of the study were the principles of ergonomic design of multimedia user interfaces, set out in the National Standard of Ukraine SSTU EN ISO 14915 1:2009. The problem of evaluating the ergonomic level of the multimedia presentation is considered from the standpoint of Decision Theory. To solve it, a model approach has been applied. Results. Two interrelated theoretical constructs have been developed: (1) a description of an ergonomic basic pattern for non-interactive multimedia presentations with a minimum set of static media; (2) a criterion model for assessing the ergonomic level of such presentations. The pattern has three characteristics that summarize the peculiaritys of the cognitive processing of information by a person. They are embodied by nine observable signs that can be directly evaluated. The criterion model is developed in the logic of constructing a multi-criteria model of the decision-making problem. Its key elements are a set of criteria and a set of criteria scales. The observed signs of the pattern are used as criteria. They are provided with binary scales. All wording and descriptions have a clear and unambiguous meaning. Conclusions. Two proposals are substantiated: (1) to consider a non-interactive multimedia presentation ergonomic if it has the following characteristics: suitability for the communication goal; suitability for understanding and memorization; suitability for perception; (2) To assess the ergonomic level of a multimedia presentation as acceptable if all nine criteria have been fulfilled. The developed theoretical constructs form the basis of informative feedback between teachers and students.